Основи міжнародної безпеки : методичні рекомендації до семінарських занять, самостійної та індивідуальної роботи (для здобувачів першого (бакалаврського) рівня вищої освіти спеціальності 291 «Міжнародні відносини, суспільні комунікації та регіональні студії» освітньої програми «Міжнародні відносини та регіональні студії - Панова, Ірина Олексіївна; Panova, Iryna O. (Харків : Харківський національний університет імені В.Н. Каразіна, 2023)
Видання містить програму навчальної дисципліни, методичні матеріали до семінарських занять, організаційно-методичні рекомендації до самостійної роботи здобувачів вищої освіти та проведення контролю знань, методичні рекомендації до написання науково-дослідних (індивідуальних) робіт, теоретичні питання для підготовки до підсумкового контролю. Методичні рекомендації розроблені для здобувачів вищої освіти спеціальності 291 «Міжнародні відносини, суспільні комунікації та регіональні студії».

The publication contains the program of the academic discipline, methodical materials for seminar classes, organizational and methodical recommendations for the independent work of students of higher education and conducting knowledge control, methodical recommendations for writing scientific research (individual) works, theoretical questions for preparation for the final control. Methodological recommendations are developed for students of higher education in specialty 291 "International relations, public communications and regional studies".
Basics of international security: methodological recommendations for seminar classes, independent and individual work (for applicants of the first (bachelor) level of higher education, specialty 291 "International relations, public communications and regional studies" of the educational program "International relations and regional studies"
Навчальне видання. В авторській редакції.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; Research Subject Categories::SOCIAL SCIENCES; міжнародна безпека; міжнародний конфлікт; міжнародний правопорядок; міжнародна воєнна безпека; міжнародна економічна безпека; міжнародна інформаційна безпека; міжнародна екологічна безпека; міжнародна ядерна та радіаційна безпека; міжнародна соціальна безпека; міжнародно-правовий режим протидії тероризму; Українська держава у системі міжнародної безпеки; складові елементи системи міжнародної безпеки; роль і значення людського фактору; глобалізація; стадії формування загроз та небезпек; нормативно-правова база; суспільні безпекові відносини; пріоритетні національні інтереси України; семінарські заняття; самостійна та індивідуальна робота; суспільні комунікації; регіональні студії; основи міжнародної безпеки; міжнародні відносини; міжнародне співробітництво; international security; international conflict; international legal order; international military security; international economic security; international information security; international environmental security; international nuclear and radiation safety; international social security; the international legal regime of combating terrorism; The Ukrainian state in the system of international security; components of the international security system; the role and importance of the human factor; globalization; stages of formation of threats and dangers; regulatory framework; social security relations; priority national interests of Ukraine; independent and individual work; seminar classes; public communications; regional studies; foundations of international security; international relations; international cooperation